International financial reporting standard (IFRS) regulations for supply chain management - Kulikova, L.I.; Gubaidullina, A.R.; Mukhametzyanov, R.Z.; Druzhilovskaya, T.U.; Druzhilovskaya, E.S. (International Journal of Supply Chain Management, 2020)
Abstract— The purpose of this study was to investigate the adaptation of International Financial Reporting Standards (IFRS) in supply chain management. This article provides a comprehensive critical analysis of the provisions of IFRS for accounting for intangible assets from the point of view of their practical application in supply chain. The objects of the study were Russian companies, because generally while composing financial statements in accordance with IFRS, there might be problems of accounting for intangible assets due to the imperfection of these regulations. The authors studied the consolidated financial statements of the 40 largest Russian organizations of the non-financial sector, composed for 2014 - 2017. As a result, there have been disclosed a number of IFRS regulations on supply chain for intangible assets, leading to significant problems in their practical application by modern organizations. The main conflicting points were the definition of intangible assets, the regulation of their valuation, the determination of the depreciation method, the ratio of goodwill and intangible assets, the presentation of general information about this type of asset. The imperfection of the regulations of IFRS on supply chain leads to the incomparability of the information presented, which negatively affects the adoption of economic decisions. The article presents options for solving the disclosed problems in order to minimize the risk of distortion of financial statements and increase the usefulness and reliability for its users.